The Effect of Pregabalin on the Minimum Alveolar Concentration of Sevoflurane: A Randomized, Placebo-Controlled, Double-Blind Clinical Trial - Müller, Johannes; Plöchl, Walter; Mühlbacher, Paul; Graf, Alexandra; Stimpfl, Thomas; Hamp, Thomas (Frontiers in Medicine, 2022)
Background: Pregabalin is commonly used perioperatively to reduce postoperative pain and opioid consumption and to prevent the development of chronic pain. It has been shown to reduce anesthetic consumption in balanced anesthesia, but studies investigating its effect on the minimum alveolar concentration (MAC) of volatile anesthetics are lacking. The aim of this study was to investigate the effect of two different doses of pregabalin on the MAC of sevoflurane. Methods: In a randomized, double-blinded, placebo controlled clinical study, 75 patients were assigned to receive placebo, 300 mg pregabalin, or 150 mg pregabalin, as a capsule one hour before anesthesia induction with sevoflurane only. After equilibration, the response to skin incision (movement vs. nonmovement) was monitored. The MAC was assessed using an up- and down-titration method. Results: The MAC of sevoflurane was estimated as 2.16% (95% CI, 2.07–2.32%) in the placebo group, 1.44% (95% CI, 1.26–1.70%) in the 300 mg pregabalin group, and 1.81% (95% CI, 1.49–2.13%) in the 150 mg pregabalin group. We therefore report a 33% reduction in the MAC of sevoflurane in the 300 mg pregabalin group as compared to placebo. The MAC of the 150 mg pregabalin group was reduced by 16% as compared to placebo but was not statistically significant. Conclusions: The administration of 300 mg pregabalin reduced the MAC of sevoflurane by 33%, while the administration of 150 mg pregabalin did not significantly reduce the MAC of sevoflurane. Pregabalin use led to a small reduction in postoperative pain levels but increased side effects in a dose-dependent manner.